2011
DOI: 10.1123/jpah.8.6.775
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, Prevalence, and Perceived Personal Barriers Toward Physical Activity Among Adult Saudis in Al-Hassa, KSA

Abstract: Objectives:To determine patterns of physical activity (PA) along domains of work-transport-leisure among adult Saudis, sociodemographic correlates of PA and perceived personal barriers to leisure-time-related physical inactivity in Al-Hassa, KSA.Methods:A cross-sectional study in which 2176 adult Saudis attending urban and rural Primary Health centers were selected using multistage proportionate sampling method. Participants were personally interviewed to gather information regarding sociodemographics, PA patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 18 publications
1
75
3
8
Order By: Relevance
“…In this study, women were less likely than men to be physically active or to meet the ACS guidelines even after adjustment for the other socio-demographics, a finding consistent with other reports (Aparicio-Ting et al, 2012;2013). The previous difference should be considered in the presence of cultural, social barriers and motivating factors may shape the differences in PA behavior between men and women (Amin et al, 2011;Al-Otaibi, 2013), a point to be taken in promoting PA for cancer prevention for the Saudi population. Al Otaibi found that among adult Saudis who were in prime age, highly educated, employed and physically inactive, the majority of them were at precontemplation stage for PA with more external barriers and less self efficacy especially among females.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, women were less likely than men to be physically active or to meet the ACS guidelines even after adjustment for the other socio-demographics, a finding consistent with other reports (Aparicio-Ting et al, 2012;2013). The previous difference should be considered in the presence of cultural, social barriers and motivating factors may shape the differences in PA behavior between men and women (Amin et al, 2011;Al-Otaibi, 2013), a point to be taken in promoting PA for cancer prevention for the Saudi population. Al Otaibi found that among adult Saudis who were in prime age, highly educated, employed and physically inactive, the majority of them were at precontemplation stage for PA with more external barriers and less self efficacy especially among females.…”
Section: Discussionmentioning
confidence: 99%
“…The previous finding is consistent with previous reports (Aparicio-Ting et al, 2012;2013) where retirees were found more likely to be active with more leisure time and more likely to be active at levels recommended for cancer prevention. Sufficient leisure activity to reduce cancer risk is likely associated with greater barriers related to time, competing commitments and motivation than participating in the lower levels required for general health benefits (Amin et al, 2011;Al-Otaibi, 2013). Perceived benefits are another important component to encourage PA behavior, increasing public awareness of the PA guidelines relevant to cancer prevention may encourage individuals to comply with these guidelines for being physically active.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations